Analisis Strategi Persediaan Bahan Baku Buah Pala Untuk Meningkatkan Efisiensi Rantai Pasok CV Cielofood Pratama di Kota Bogor - Nopita Sari Hutabarat; Salsabila Dwi Putri; Intan Pijar Azzahra; Atsiilah Dwi Kurnia Pratiwi; Muhammad Abdurrahman; Wawan Oktariza; Tina Nur Ainun (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
CV Cielofood Pratama is a beverage processing business with nutmeg raw materials, located in Bogor City, West Java. The company produces syrups with varying sizes of packaging. The multi-stage production process does not rule out the possibility of irregularities that could cause the product to no longer meet the quality standards we set. In general, business units have a profit goal for business sustainability, by seeking efficiency in operations in order to obtain profitable profits. Analysis of the data shows the difference between corporate policy and the results of the EOQ method. The company usually orders 25 kg of raw materials with a frequency of 120 times per year. However, the EOQ method recommends ordering 144 kg with a frequency of 36 times per year. In addition, there is a significant difference in the total cost of supplies, which is IDR 30,900,000 according to company policy and IDR 10,392,000 according to EOQ method. This study aims to analyze strategies in raw material supply as an effort for supply chain efficiency. Using the Economic Orders Quantity (EOQ) method Reduce storage costs, save space on both storage and workspaces, resolve problems and reduce the risk that raw material supplies may pose.